Past, present, and future of CASS educational programs and initiatives - Rokhani, Fakhrul Zaman; Zhang, Xinmiao; Joshi, Rajiv V.; Reis, Ricardo; Grimblatt, Victor; Tang, Kea-Tiong; Li, Yongfu; Amara, Amara; Delgado-Restituto, Manuel (Institute of Electrical and Electronics Engineers, 2024)
The Circuits and Systems Society (CASS) places a strong emphasis on advancing education within its domain. Various educational programs and resources have contributed to the professional development of CASS members for more than 20 years now. A major transformation within the Society was started in 2021 with a clear vision to become a premier educational resource within circuits and systems areas of interest. This article provides a comprehensive review of flagship educational programs and past initiatives. Insights from the lessons learned and future trends in the education ecosystem guided society's strategies and frameworks for improving and developing new educational products and services. The benefits of learning with the CASS program are presented, highlighting the Society's deep commitment to serving the community at large in educational pursuit for years to come.